2002
DOI: 10.5993/ajhb.26.6.6
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Behaviors Associated With Adolescent Violence and Aggression

Abstract: To explore risk factors and behaviors associated with aggressive and violent behaviors among adolescents. Methods: A comprehensive review of research literature from various disciplines associated with improving the health and well-being of adolescents. Results: Risk factors and behaviors associated with adolescent aggression and violence are discussed via 6 major factor categories: individual, family, school/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 66 publications
9
114
0
5
Order By: Relevance
“…[1][2][3][4] Current study findings are also consistent with substantial research indicating that violence experienced during adolescence increases risk for involvement in high risk behaviors such as criminal activity/deviance, 3,31 drug and alcohol use, 14,22,23 and violence perpetration, [32][33][34] as well as a number of negative health and psychosocial effects 19,20,22,35 in adulthood. More specifically, a number of studies focusing on street violence involvement as well as violence perpetrated against an intimate partner have highlighted men's previous experiences as victims to be a significant factor driving these forms of violence perpetration later in life.…”
Section: Discussionsupporting
confidence: 72%
“…[1][2][3][4] Current study findings are also consistent with substantial research indicating that violence experienced during adolescence increases risk for involvement in high risk behaviors such as criminal activity/deviance, 3,31 drug and alcohol use, 14,22,23 and violence perpetration, [32][33][34] as well as a number of negative health and psychosocial effects 19,20,22,35 in adulthood. More specifically, a number of studies focusing on street violence involvement as well as violence perpetrated against an intimate partner have highlighted men's previous experiences as victims to be a significant factor driving these forms of violence perpetration later in life.…”
Section: Discussionsupporting
confidence: 72%
“…Adolescents' violent behaviors include weapon carrying (e.g. gun, knife, or club), physical fight, relationship violence, peer violence, school violence such as bullying, slapping, or punching to weapon use, and suicidal behaviors (ideation and attempts) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide rates have seen the most dramatic increase (39%) within the 10-to 14-year-old age range during the past 20 years (Centers for Disease Control and Prevention [CDC], 2001). Studies have shown that adolescent risk behaviors tend to cluster or overlap (Donovan & Jessor, 1985;Dryfoos, 1990;Osgood, Johnston, & O'Malley, 1988), particularly in the areas of substance use, sexual risk-taking, and violence Valois, MacDonald, Bretous, & Fischer, 2002;Valois, Oeltmann, Hussey, & Waller, 1999), and more than likely, youth developmental assets (Reininger et al, 2003). Teenagers today reach puberty two or three years earlier than in 1900, and young people have vastly increased access to improved transportation and communication technologies.…”
Section: Selected Health Risk Behaviorsmentioning
confidence: 99%